2005
DOI: 10.1128/cmr.18.3.423-445.2005
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Potential of the Microsporidia

Abstract: Microsporidia are long-known parasitic organisms of almost every animal group, including invertebrates and vertebrates. Microsporidia emerged as important opportunistic pathogens in humans when AIDS became pandemic and, more recently, have also increasingly been detected in otherwise immunocompromised patients, including organ transplant recipients, and in immunocompetent persons with corneal infection or diarrhea. Two species causing rare infections in humans, Encephalitozoon cuniculi and Brachiola vesicularu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
427
1
30

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 419 publications
(466 citation statements)
references
References 296 publications
(272 reference statements)
8
427
1
30
Order By: Relevance
“…Regarding the result that anti-E. cuniculi IgG antibodies were detected at 75.2% in group II, a finding similar to this was also found in a survey of 100 New Zealand White rabbits maintained in a research colony, in which 72% of the animals showed renal lesions and in which parasites were identified in 9% [14], supporting our decision for having grouped our 337 healthy rabbits into two groups, i.e., groups I and II. The suggestion that E. cuniculi can be transmitted by ingestion of spores excreted in urine [10] seemed plausible in positive rabbits in group II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the result that anti-E. cuniculi IgG antibodies were detected at 75.2% in group II, a finding similar to this was also found in a survey of 100 New Zealand White rabbits maintained in a research colony, in which 72% of the animals showed renal lesions and in which parasites were identified in 9% [14], supporting our decision for having grouped our 337 healthy rabbits into two groups, i.e., groups I and II. The suggestion that E. cuniculi can be transmitted by ingestion of spores excreted in urine [10] seemed plausible in positive rabbits in group II.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the United Kingdom, Harcourt-Brown and Holloway [6] reported a rate of detection of anti-E. cuniculi IgG antibodies among 38 asymptomatic rabbits of 36.8%. In Switzerland, Mathis et al [10] reported that anti-E. cuniculi IgG antibodies were detectable in 7.5% of 292 asymptomatic rabbits. Nevertheless, in this study of the 74 rabbits in group I, regarded as examples of healthy and isolated rabbits, a detection rate of anti-E. cuniculi IgG antibodies of 29.7% was found.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, these obligate intracellular parasites have long been recognized as pathogens in animal industries, first in silkworms in 1857, then in honeybees more than a century ago. They were later found in fish and more recently in mammals (reviewed in Mathis et al, 2005). Prior to the middle of the 1980's only sporadic cases of microsporidia infections were well documented in humans (reviewed in Weber et al, 1994).…”
mentioning
confidence: 99%
“…It is thought that many possible infections might be overlooked due to not only insufficient focus on microsporidiosis in the differential diagnosis of infections but also difficulties in detection of Microsporidia spp. in laboratory investigations (1)(2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
“…(1,2). In recent studies using genetic analyses, the zoonotic potential has clearly been documented about these parasites (3).…”
Section: Introductionmentioning
confidence: 99%